Long-Term Effects of Short-Term Music Therapy for Prison Inmates: Six-Year Follow-Up of a Randomized Controlled Trial - Assmus, Jörg (International journal of offender therapy and comparative criminology, 2021)
For most interventions to reduce criminal recidivism, long-term effects are uncertain. Music therapy has shown effects on possible precursors of recidivism, but direct evidence on long-term effects is lacking. In an exploratory parallel randomized controlled trial, 66 inmates in a Norwegian prison were allocated to music therapy or standard care and followed up over a median of 6 years, using state registry data. Median time to relapse was 5 years, with no differences between the interventions. The imprisonment of most participants was too short to provide a sufficient number of therapy sessions. Sufficiently powered studies are needed to examine the long-term effects of appropriate doses of therapy.